PENGGUNAAN MODEL PEMBELAJARAN BLENDED LEARNING PADA ERA REVOLUSI INDUSTRI 4.0 - Said Ahmad Zulfi Fathullah (JURNAL SOCIUS, 2020)
Learning in the Industrial Revolution Era 4.0 requires teachers to be able to use technology, information, and communication. Teachers are required to have knowledge of technology as their teaching skills by applying blended learning models so that students are interested in participating in the learning process. Blended learning model has its own advantages and disadvantages, but this model is very appropriate to be used in the era of the industrial revolution 4.0 while supporting the theory of cybernetics learning which is relatively new compared to existing learning theories, in line with developments in technology and information science.Pembelajaran pada Era Revolusi Industri 4.0 mengharuskan guru mampu menggunakan teknologi, informasi, dan komunikasi. Guru dituntut untuk memiliki pengetahuan akan teknologi sebagai keterampilan mengajarnya dengan menerapkan model pembelajaran blended learning sehingga peserta didik tertarik untuk mengikuti proses pembelajaran. Model pembelajaran blended learning memiliki berbagai kelebihan dan kekurangan tersendiri, tetapi model ini sangat tepat digunakan pada era revolusi industri 4.0 sekaligus mendukung teori belajar sibernetik yang relatif baru dibandingkan dengan teori belajar yang telah ada, sejalan dengan perkembangan teknologi dan ilmu informasi.